A test of the impact of pain on automatic motivational processes in people with knee osteoarthritis. (November 2022) - Nguyen Luong, My-Linh; Bennell, Kim L.; Hinman, Rana S.; Rebar, Amanda L.
Abstract: Objective: People with osteoarthritis are likely to be physically inactive and current socio-cognitive approaches to changing physical activity in this patient population are generally ineffective. We assessed prospective associations between physical activity and the automatic processes of habit automaticity, automatic evaluations, and automatic self-schema in people with knee osteoarthritis. Design: One-week prospective. Method: 253 adults (aged 46–82 years, 72% female, 28% male) with knee osteoarthritis self-reported their physical activity behaviour of the past week, habit automaticity for physical activity and completed two implicit association tests to assess automatic evaluations of physical activity (relative to sedentary behaviour) and automatic self-schema for physical activity. One week later, participants self-reported physical activity and pain while walking over the prior week. Linear regression models assessed associations of each automatic process with subsequent physical activity and the moderation effect of pain and each automatic process on subsequent physical activity, controlling for covariates. Results: We did not find evidence of a statistical relationship between physical activity with automatic evaluations, automatic self-schema, or habit automaticity. The inclusion of pain while walking did not moderate the relationship between any automatic process and physical activity. Conclusion: Although previous research on healthy, young adults suggests that automatic processes affect physical activity behaviour, we did not find evidence to confirm whether a similar relationship exists for older adults with knee osteoarthritis. Replication and extension work testing these research questions is needed to ensure the findings are not a result of measurement and design features of the study. Highlights: There was no evidence that knee pain while walking impacts how automatic processes affect physical activity. Habit, implicit attitudes, and self-schema were not related to physical activity in older adults with osteoarthritis. Given the paucity of anticipated correlates with the physical activity outcome, caution is needed before concluding that these findings reflect real-world experiences.